Improving discovery and access of your data: a technical demonstration - Milward, Adam (International Journal of Population Data Science, 2025)
Objectives We aim to raise awareness of the latest tools and processes available to manage data access, allowing users to improve efficiency and utility while harnessing the power of their data for good. Method A technical demonstration which focuses on the data user journey from discovery to access, showcasing an early use case developed by MetadataWorks in partnership with the ONS. We will demonstrate key features of the tool, live searching the catalogue, requesting data access and managing requests. We will look at the process from the perspective of both the user and the data owner. We then interrogate how to implement similar projects with some best practice notes, allowing attendees to get more from their own data. Results The project is currently in its infancy, though we anticipate the results of implementing the tools and process we outline in the session to include 1) reducing the speed of processing data access requests, 2) reducing the effort required by the data owner and 3) an improved user experience for the requestor. In turn, these improvements will increase the visibility and utility of data sets and encourage our ultimate goal of using our data for good. Conclusion Attendees will leave the presentation with pragmatic tips and advice regarding upgrading their tools and processes to meet best practice standards in managing data access.